"Cell Phones Under the Table": Meeting Students' Needs to Reduce Off-Task Smartphone Use Through Faculty–Student Collaboration. (June 2021) - Batch, Brook; Roberts, Jacqueline; Nakonechnyi, Alex; Allen, Rebecca
While technology offers educators many affordances to provide students with rich educational experiences, literature and empirical experience indicates that students' unstructured cell phone usage may have adverse impacts on student achievement and create a contagious climate of distraction. This research project seeks to understand students' unstructured cell phone usage, faculty response, and foster improved student–faculty communication to determine concrete interventions to off-task smartphone usage. For the purposes of this study, we surveyed and interviewed faculty and undergraduate students at two small private universities in the United States. Findings suggest that students and faculty recognize the limitations of punitive cell phone policies and desire intervention. Giving students' movement alternatives and offering faculty more training in using smartphones as educational tools may be acceptable solutions.